2014
DOI: 10.2174/1874350101407010029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Emotional Disorders Among Students of University of Medical Sciences; Iran

Abstract: Background: No nation-wide data are available on mental disorders in medical students. Such information can be useful for having a proper approach to and intervention for our students' health condition. Aim: To determine the mental health status in all of the students who study in one medical university. Methods: After invitation of all 790 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…One hundred ninety-five studies involving a total of 129 123 individuals in 47 countries were included in the analysis (Figure 1). The median number of participants per study was 336 (range, 44-10 140).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred ninety-five studies involving a total of 129 123 individuals in 47 countries were included in the analysis (Figure 1). The median number of participants per study was 336 (range, 44-10 140).…”
Section: Resultsmentioning
confidence: 99%
“…The median number of participants per study was 336 (range, 44-10 140). One hundred sixty-seven cross-sectional studies (n = 116 628) and 16 longitudinal studies (n = 5728) in 43 countries reported on depression or depressive symptom prevalence (Table 1). Twenty-four cross-sectional studies (n = 21 002) in 15 countries reported on the prevalence of suicidal ideation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This tool is well potent to distinguish sleep disorders such as primary insomnia, major depression and daytime over sleepiness from normal sleep [5,6]. The PSQI-P is constructed of seven parts based on international classification of sleep disorders to find sufferers in a period of last four weeks [5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore depression in this stage of life can lead to some negative consequences that affect the other stages of the life. Although this study did not show a significant relationship between mental health and individualism, the increasing prevalence of mental disorders among students in comparison with general population in Iran should not be ignored (Akbari et al , 2014). It seems that individual-level mental health is toughly mediated by the context in which students live and perform their daily activities.…”
Section: Discussionmentioning
confidence: 62%
“…According to WHO, approximately half of the population of the world would be affected by mental disorders by the year 2020 (Storrie et al , 2010; Noohi et al , 2013). Also, it is predicted that mental disorders would be one of the largest contributors to the global burden of disease by the year 2020 (Akbari et al , 2014; Yazdi Feyzabadi et al , 2015).…”
Section: Introductionmentioning
confidence: 99%